The Impact of Product Market Competition on Employment and Wages - Bruno Amable; Donatella Gatti (Institute for the Study of Labor (IZA), 2001)
Standard economic wisdom generally stresses the benefits of increased competition on the product market. This paper proposes a model of monopolistic competition with an endogenous determination of workers flows in and out of unemployment, where wages are determined according to an efficiency wage mechanism. We show that an increase in product market competition boosts the hiring rate as well as the separation rate. Hence, the efficiency wage schedule compatible with more competition shifts upward. An adverse effect on workers? incentive is at work which pushes real wages up to the point that increased competition may indeed generate employment losses rather than gains.
Keywords: E24; J41; J63; L13; 330; Unemployment; efficiency wage; imperfect competition; Monopolistischer Wettbewerb; Arbeitsmarkttheorie; Theorie der Arbeitslosigkeit; Effizienzlohn; Mehr-Sektoren-Modell; Theorie